2020
DOI: 10.1016/j.jcomm.2020.100124
|View full text |Cite
|
Sign up to set email alerts
|

Stock market response to potash mine disasters

Abstract: We examine the stock market reaction to natural and man-made disasters in potash mines. We use a sample of 44 mining accidents worldwide over the period 1995-2016. A quarter of the accidents were the result of a natural disaster, such as flooding, that often ended in the closure of the potash mine. The remaining accidents were caused mainly by human error, and almost 50% were work accidents often associated with serious injury or death. On average, mining firms experience a drop in their market value of 0.89% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 18 publications
3
43
1
Order By: Relevance
“…Bash and Alsaifi (2019) studied the impact of the murder of Jamal Khashoggi on the Saudi Stock Exchange and found that the event has raised a high risk of uncertainty with abnormal cumulative returns. Unlike the previous studies, Kowalewski and Spiewanowski (2020) studied the effects of mining disaster on the mining stock and found that media coverage on the mining disaster resulted in a decline of 1.15% firm value.…”
Section: Literature Evidencementioning
confidence: 94%
“…Bash and Alsaifi (2019) studied the impact of the murder of Jamal Khashoggi on the Saudi Stock Exchange and found that the event has raised a high risk of uncertainty with abnormal cumulative returns. Unlike the previous studies, Kowalewski and Spiewanowski (2020) studied the effects of mining disaster on the mining stock and found that media coverage on the mining disaster resulted in a decline of 1.15% firm value.…”
Section: Literature Evidencementioning
confidence: 94%
“…As a result, there is no consensus in the literature on how stock returns respond to such disasters. Previous studies have extensively examined the effects of disasters on stock prices (Kowalewski and Śpiewanowski 2020;Donadelli et al 2020;Cross 1992, 1990). Shelor, Anderson, and Cross (1990), (1992)) find a negative impact on stock returns of real estate firms due to an earthquake in California.…”
Section: Introductionmentioning
confidence: 99%
“…Using granular analysis, Donadelli et al (2020) show that tornados have a negative effect on stock returns in the US. In a recent paper, Kowalewski and Śpiewanowski (2020) investigate how stock markets respond to disasters in potash mines, using data on 55 mining accidents worldwide between 1986 and 2019. They illustrate that the market value of these mining firms drops by 1.15% over the first 2 days of the accident.…”
Section: Introductionmentioning
confidence: 99%
“…Methodological difficulties as well as the evolving architecture of commodities markets appear to be at play. For example, an analysis of stock market response to potash mine accidents revealed substantial heterogeneity of investors' reactions with disasters of natural origin (seemingly less predictable) precipitating a more significant correction of mining firms' stocks than man-made accidents [31]. Petrochemical companies' stocks similarly experience a significant decline (ca.…”
Section: Literature Reviewmentioning
confidence: 99%